Distribution and Diversity Patterns of Amphibian Species in the Rajah Sikatuna Protected Landscape, Bohol, Philippines (Journal of Biodiversity Conservation and Bioresource Management, 2022)
This recent study conducted at Rajah Sikatuna Protected Landscape, Bohol, Philippines (RSPL) from August to October 2019 resulted to a total of 17 amphibian species belonging to 7 families; of these species, two (2) are near threatened, 11 are Philippine endemics, five (5) are native, and one (1) introduced/non-native. Barangay Bugsoc had the highest diversity H (2.09) as well as species richness (10); Barangay Omjon also had a species richness of 10, both of these areas are forested and riparian areas. Abundance of the number of individuals and number of species geared towards mixed vegetation forest and riparian areas at elevation ranging from 400-600 masl. High species diversity, evenness and richness (Shannon-Weiner, Shannon evenness and Menhinick richness indices) were observed on areas with minimal anthropogenic disturbance. The distribution pattern can be linked to the influence of resource accessibility and microclimatic conditions available for direct utilization by the species. Conversely, areas with high disturbance, such as agricultural and grassland areas, showed high dominance of Rhinella marina, an introduced species.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 23-32